Merancang Dan Analisa Pengukuran Tahanan Pembumian Dengan Menggunakan Elektroda Ground Steel Wire Pada Gedung Kuliah Terpadu III Politeknik Negeri Bengkalis - Tarmizi, Tarmizi; Agustiawan, Agustiawan (Politeknik Negeri Bengkalis, 2022)
The grounding system is part of the electrical installation that functions tosecure electrical equipment and humans. This grounding system has low impedanceproperties, so that the overcurrent in the installation network can be flowed quickly tothe ground so as to minimize damage to equipment in the building and protect thepeople inside it. Bengkalis State Polytechnic is a State University located in BengkalisRegency, Riau Province, from year to year there has been a very good increase, startingfrom the number of study programs and the number of students, each year the numberof new students who are interested is increasing, therefore Bengkalis State Polytechnictook the opportunity to build the Integrated Lecture Building III. Indonesia. To securethe Integrated Lecture III Building from lightning strikes, it is necessary to provideprotection media to make grounding or grounding using rod electrodes so that thebuilding can be protected from danger and reduce the occurrence of damage toelectrical or electrical equipment inside the Integrated Lecture III building. The resultsof grounding measurements are measured using an Earth Tester with a distancebetween PCs or iron poles of 1 meter with a grounding resistance value of 3.5 ohm .Keywords: Grounding system, Integrated Lecture Building III Bengkalis StatePolytechnic.